Student Perception of Blended Learning in Learning English - Randy Irawan; Muhamad Aminullah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The purpose of this study was to determine students' perceptions of the application of Blended Learning, namely the use of Microsoft Teams in English Learning in class XI (Eleventh). This study used a quantitative survey approach which spent two months collecting data using an online closed-ended questionnaire. Data was taken from students of class XI (Eleventh) consisting of 71 respondents from a total of 181 students using Random Sampling. To determine student perceptions, the scores obtained from the closed-ended questionnaire were converted into percentages for analysis. The results of this study showed that students gave their positive perceptions of the use of Blended Learning using Microsoft Teams in English Learning. Respondents' positive ratings were obtained from their experience in learning using Microsoft Teams. They are enjoy with using Microsoft Teams which has many features and is easy to use. This research also reveals that Blended Learning using Microsoft Teams is very beneficial for them. Blended Learning makes learning not boring, they are more interested in learning. In addition, being more active and being able to add insight that is getting wider because it has many features that are very useful for students.